(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Simmondsia chinensis Schneider commonly known as jojoba is a semi-arid evergreen shrub. Jojoba is unique among plants in the fact that its products (seeds) contain about 50 percent by weight oil. Jojoba liquid wax generally used in folk remedies for renal colic, sunburn, chaffed skin, hair loss, headache, wounds and sore throat. However, there are no reports on the roots of this plant. The present investigation deals with the pharmacognostical studies of the roots of the said plant. Pharmacognostical studies include microscopic, physico-chemical constants (ash & extractive values), fluorescence analysis and preliminary phytochemical evaluation.